The Development of Android-Based Arabic Language Environmental Materials in Islamic Boarding School (Ma’had) - Muhammad Yusuf Salam; Muhammad Husni Shidqi; Adam Mudinillah; Oliva Levan’s (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
The aim of this research was (1) to fulfill the need for Android-based Bi`ah Arabiyah material, (2) to ensure the suitability of Android-based Bi'ah Arabiyah material, and (3) to test the practicality of Android-based Bi'ah Arabiyah material. The research method used is 4D model R&D research through four stages, namely defining, designing, developing, and disseminating. The research that the researcher conducted only reached the 3 D stages, namely define, design, and develop. The results of this research are that the test subjects in this research were 12 first semester students using Aiken V with a minimum validity and practicality value of 71. Quantitative descriptive data analysis techniques are employed in qualitative data analysis methods. The results of the research show that material designed using Android can be used and applied in Ma'had 'Ali Syekh Sulaiman Araasuli Agam, West Sumatra, with language validation provisions with a score of 92.5, while for material validation with a score of 84.6 and for media validation with a score of 86.6, so that under these conditions the material designed is suitable for dissemination.